Stimulating Thinking through Thinking Techniques: Commitment Proposals that Enrich a Centre’s Potential for Innovation - Escamilla, Amparo; Grandal, María del Mar; Randell, David; Castilla, Paula María; García, Rocío; Gómez, Constanza; González, Rocío; Muñoz, Manuel; Álvarez, Sonia; de la Riva, José Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
The commitment of a whole teaching centre to promote thinking skills as part of their innovation approach is both positive and achievable. Thinking skills provide enriching experiences that promote cooperation and allow participants to develop teaching from a shared compromise as outlined in the Teaching Centre Development Plan. The range of proposals made by different Departments highlight how working together with a common objective and applying the same skills across the curriculum enriches both teaching and learning. In this context learning to think becomes an essential part of learning to learn.